Nemo phosphorylates Even-skipped and promotes Eve-mediated repression of odd-skipped in even parasegments during Drosophila embryogenesis. - Braid, L.R.; Lee, W.; Uetrecht, A.C.; Swarup, S.; Papaianni, G.; Heiler, A.; Verheyen, E.M. (Developmental Biology, 2010)
Drosophila nemo (nmo) and other Nemo-like kinase family members (Nlks) are well-established key regulators of numerous conserved signaling pathways, such as Wg and BMP. nmo mutants display pleiotropic defects at different developmental stages, including the embryo. In this study we describe a detailed characterization of embryonic cuticle patterning defects associated with maternal loss of nmo. nmo mutant embryos consistently show segmentation defects, most frequently fusions of pairs of denticle belts in alternating segments. These phenotypes are reminiscent of those associated with defects in pair-rule patterning. Genetic interaction studies demonstrate that Nmo promotes Even-skipped (Eve) activity and is required to promote the expression of the Eve target, engrailed (en), in even numbered parasegments. We find that Nmo regulates a subset of Eve activities by stimulating Eve-mediated suppression of the odd-skipped (odd) repressor. Furthermore, we isolate Nmo in a protein complex with Eve and show that Nmo phosphorylates Eve in in vitro kinase assays. These studies reveal a novel role for the Nmo kinase in embryonic pattern formation through its regulation of the homeodomain-containing transcription factor Eve.